Old Age Poverty in Selected Countries of the European Community- Are Women Disproportionably Affected? - Heinz Stapf-Finé (Luxembourg Income Study (LIS), 1994)
This paper details the institutional structure of compensations to the elderly for interruptions of working life and for non-market (family) work as well as the various forms of minimum pensions for six LIS countries. Comparisons are then made using poverty rates and poverty gaps as to the extent these described provisions contribute to the prevention of the 'feminization of poverty' in old age.
Keywords: 330